PENGARUH PRODUK DOMESTIK BRUTO DAN INFLASI TERHADAP JUMLAH DEPOSITO BERJANGKA PADA BANK PANIN TAHUN 2011 - 2015 - Selfia Karolina Silitonga; Rosyetti '; Ando Fahda Aulia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of the Gross Domestic Product and Inflation on time deposit at Bank Panin in 2011-2015. This study is an analysis of secondary data to analyze the effect of the Gross Domestic Product and Inflation against time deposit at Bank Panin in 2011-2015. The data used in this research is data time series data are sourced from Panin Bank and the Central Bureau of Statistics. Methods of analysis which used is the method of multiple linear regression analysis with SPSS version 21.00. Tests conducted on the hypothesis and the reliability of the data (assuming classical) using a 5% significance level. From the results of tests performed on this research can be concluded that the independent variable is the variable gross domestic product and inflation together with the F test significant effect on the amount of deposit is equal to 0.000. Individually variable Gross Domestic Product positive and significant effect against amount of time deposits and variable inflation has a negative effect and no significant effect on the amount of deposit. The results of the coefficient of determination (Adjusted R2) of the independent variable on the dependent variable obtained a value of 85.4%, while the remaining 14.6% is influenced by other variables not included in this study.Keywords: gross domestic product, inflation and time deposit.